2016
DOI: 10.1177/1049732316628835
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Personal and Social Identity With Type 1 Diabetes During Adolescence

Abstract: This study explored the incorporation of type 1 diabetes mellitus (T1DM) into self-identity among adolescents. Guided interviews explored 40 adolescents' views of T1DM in relation to their sense of self and relationships with others. Responses were analyzed using thematic analysis. Results revealed that the entire sample described T1DM as a significant burden; many described how T1DM made them feel less "normal." Adolescents described both positive and negative aspects of self-management in social relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 45 publications
(64 reference statements)
5
82
2
Order By: Relevance
“…In addition to the changes in everyday life due to diabetes, the results of this study show that concern about and fear of disease-related complications and previous negative experiences lived by them or by family members due to poor knowledge of the disease can have a negative impact on the lives of pre-adolescents with T1D. One study (4) found that, as a result of pre-adolescents not receiving adequate support in the transition phase from childhood to adolescence, many of them focused on negative aspects and difficulties of coping with the management of the disease, which led to obstacles to addressing their therapeutic needs.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…In addition to the changes in everyday life due to diabetes, the results of this study show that concern about and fear of disease-related complications and previous negative experiences lived by them or by family members due to poor knowledge of the disease can have a negative impact on the lives of pre-adolescents with T1D. One study (4) found that, as a result of pre-adolescents not receiving adequate support in the transition phase from childhood to adolescence, many of them focused on negative aspects and difficulties of coping with the management of the disease, which led to obstacles to addressing their therapeutic needs.…”
Section: Discussionmentioning
confidence: 73%
“…With self-care support, pre-adolescents with T1D can assume a leading role in their care, rendering this approach effective in preparing this population for the management of their own health during the transition from childhood to adolescence (4) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because patients with type 1 diabetes cannot face the "stigma" of diabetes, they tend to refuse to use insulin. In addition, the younger the patients are at the onset of type 1 diabetes, the more susceptible they are to stigma because the disease forces them to have a different lifestyle (Commissariat et al, 2016). 7 The characteristics of patients with type 1 diabetes in Japan are (i) relatively low age of onset, (ii) small disease population, and (iii) required insulin supplementation for the rest of their lives.…”
mentioning
confidence: 99%